A new endoscopic scoring system corresponding to histological healing using linked color imaging in ulcerative colitis: the SOUL study - Saito, Daisuke; Hirai, Fumihito; Uchiyama, Kazuhiko; Takagi, Tomohisa; Naito, Yuji; Takatsu, Noritaka; Tanabe, Hiroshi; Kishimoto, Mitsuo; Matsuura, Minoru; Miyoshi, Jun; Watanabe, Kenji; Esaki, Motohiro; Naganuma, Makoto; Hisamatsu, Tadakazu (Endoscopy International Open, 2023)
Background and study aims An important therapeutic aim in ulcerative colitis (UC) is endoscopic remission. Although an endoscopic score with white light imaging (WLI) is mainly used to evaluate endoscopic findings, the usefulness of linked color imaging (LCI) has been reported. We evaluated the relationship between LCI and histopathological findings and attempted to establish a new LCI endoscopic evaluation index for UC.Patients and methods This study was conducted at Kyorin University, Kyoto Prefectural University, and Fukuoka University Chikushi Hospital. Ninety-two patients with a Mayo endoscopic subscore (MES) ≤ 1 who underwent colonoscopy for UC in clinical remission were included. LCI index was defined as redness (R) (Grade 0–2), area of inflammation (A) (Grade 0–3), and lymphoid follicles (L) (Grade 0–3). Histological healing was defined as Geboes score < 2B.1. Endoscopic and histopathological scores were determined by central judgment.Results In 92 patients, 85 biopsies from the sigmoid colon and 84 biopsies from the rectum (total 169 biopsies) were evaluated. There were 22, 117, and 30 cases of Grades 0, 1, and 2, respectively in LCI index-R; 113, 34, 17, and five cases of Grades 0, 1, 2, and 3, respectively, in LCI index-A; and 124, 27, 14, and four cases of Grades 0, 1, 2, and 3, respectively, in LCI index-L. Histological healing was achieved in 84.0 % of the cases (142 of 169), and there were significant associations with histological healing or non-healing in LCI index-R (P = 0.013) and A (P = 0.0014). Conclusions A new LCI index is useful for predicting histological healing in UC patients with MES ≤ 1 and clinical remission.